Perancangan Interior Store dan Office Brand Lokal Giyomi di Surabaya - Rininta Cahyaningtyas; Sriti Mayang Sari; Jean Francois Poilot (Intra, 2018)
Technology has become a daily necessity. This activity is usually called online shopping. Most of these activities triggered the emergence of various local brands which can compete international brand quality. Giyomi is one of Surabaya local brand that sells clothes such as shirts, blouses, cloth pants, sweaters, and others. The problem that is often experienced when shopping online is quality and size. The design purpose is to support online sales with the presence of physical store which is expected to make customers satisfy with the service of Giyomi. The designer used design thinking method. There are seven stages in the method such as Inquiry, Empathize, Define, Brainstorming, Prototype, Test, Apply and Reflection. The result of the problem solution is the concept of Explore with Us. Explore, which means looking for, imply buyers to explore the whole of the physic store and enjoy the different ways of shopping. With us, that stands for Giyomi itself, brings the value of Giyomi to the design.